HIV infection and high risk behavior among patients attending an STD referral clinic in Prague, Czech Republic - Mikl, J; Sudar, Z; Smith, P F; Bruckova, M; Jedlicka, J; Kastankova, V; Tryzna, R; DeHovitz, J (Sexually transmitted infections, 1998)
OBJECTIVE: This survey was conducted to determine the prevalence of HIV infection and associated risk behaviour in a high risk population of clients attending an STD clinic in Prague, Czech Republic. METHODS: Between September 1994 and January 1995, clients entering the Apolinar STD clinic in Prague, Czech Republic, were enrolled in a blinded, unlinked HIV antibody seroprevalence study. Non-identifying demographic characteristics, STD diagnoses, HIV risk exposures, and voluntary HIV testing experience were extracted from medical charts. RESULTS: Of 1394 patients for whom serum was available for testing, one was positive for HIV (HIV prevalence 0.07%, 95% confidence interval (CI) 0.01, 0.41%). This person was one of 28 men having sex with men (MSWM) (HIV prevalence among MSWM 3.6%, 95% CI 0.6, 17.7%). Among the 775 male clients, 75.5% had heterosexual unprotected sex, 11.1% had sex with high risk partners or prostitutes, 3.6% were MSWM, 1.0% were injecting drug users (IDUs), 0.7% were both MSWM and IDUs, and 6.8% and 1.8% had other or no recognized risk for HIV/STDs, respectively. Among the 619 female clients, 74.5% had heterosexual unprotected sex, 11.6% were prostitutes, 7.8% had sex with high risk partners, 1.1% were IDUs, and 3.9% and 2.3% had other or no recognised risk, respectively. The 304 adolescent patients (age 11-19 years) differed significantly (p < 0.05) in risk behaviour and STD diagnoses from the 1090 patients who were 20 years and older. Adolescents were significantly more likely to be female (58.6% v 40.5%, OR = 2.1), IDUs (3.6% v 0.4%, OR = 10.2), prostitutes (8.9% v 4.7%, OR = 2.0), and have sex partners with STDs (7.6% v 4.4%, OR = 1.8). The adolescent patients were also significantly more likely to be diagnosed with gonorrhoea (21.1% v 12.3%, OR = 1.9) and non-gonococcal urethritis (27.6% v 17.2%, OR = 1.8), and significantly less likely to have been tested previously for HIV (19.1% v 31.9%, OR = 0.5). CONCLUSIONS: HIV infection is currently uncommon in this population. However, the high rates of unprotected sex, prostitution, injecting drug use, and STDs, especially among adolescents, provide the basis for an epidemic in this population. Aggressive prevention education should be started before adolescence.
Keywords: Child; Humans; lidé; Prevalence; HIV infekce; mladiství; Age Factors; Czech Republic; lidé středního věku; HIV Infections; riskování; prevalence; Sexual Partners; Middle Aged; věkové faktory; Female; Male; Sexual Behavior; Adult; Patient Acceptance of Health Care; HIV Seropositivity; mužské pohlaví; Aged; ženské pohlaví; Cross-Sectional Studies; Substance Abuse, Intravenous; sexuální partneři; průřezové studie; dospělí; HIV séropozitivita; dítě; Česká republika; intravenózní abúzus drog; pacientův souhlas se zdravotní péčí; Risk-Taking; sexuální chování; Adolescent; senioři